Does a Scientific Initiation scholarship influence the academic performance of undergraduates? (Research, Society and Development, 2020)
Objective: This case-control study aimed to investigate whether there is an association between being a beneficiary of a scientific initiation scholarship and the academic performance of undergraduate students in Dentistry (O) and Medicine (M). Methodology: The case group (GCs) was composed of scholarship students (M = 14; O = 52) and the control group (GCt) by non-scholarship students (M = 58; O = 40), all of whom were part of the Initiation Program Scientific Research (PIC). The performance coefficients (CR) of the participants were calculated, weighted by the workload of the courses taken, considering two times: T0 - grades of the courses taken prior to insertion in the PIC and TPIC grades in the courses taken concurrently / after the 1st participation in the program. Results: After the non-parametric analysis of the data, it was found that in T0 there was no statistically significant difference between scholarship and non-scholarship students regarding CR, regardless of the course. With the admission to the PIC, regardless of having a scholarship or not, there was an increase in the median CR for dentistry students, (GCs: T0 = 7.63b; TPIC = 7.80a / GCt: T0 = 7.51b; TPIC = 7 , 64a; Wilcoxon, p